Sedimentology of the Wapiabi Formation and Equivalents (Upper Cretaceous), Central and Northern Foothills, Alberta - Ferguson, Scott G. (My University, 1984)
This thesis provides detailed sedimentological descriptions and interpretations for the Upper Cretaceous Wapiabi Formation of the central and northern Alberta Foothills. The Wapiabi Formation is made up at seven members (Muskiki, Marshybank, Dowling, Thistle, Hanson, Chungo, and Nomad) which form a thick sequence (up to 700 m) of predominantly marine shales, siltstones, and sandstones.
During Muskiki time (late Turonian to Coniacian), deposition in the Alberta Basln was largely restricted to marine shales. These shales were deposited during a period of relative orogenic quiescence in the rising Cordillera to the west.
Subsequent to deposition of the Muskiki Member, siltstones of the early Santonian aged Marshybank Member (and sandstones of its equivalent to the north, the Bad Heart Formation) were deposited. Paleocurrent data suggest that this clastic pulse prograded from the northwest. A facies change from nearshore sands to deeper marine siltstones occurs in the area just north of Hinton, Alberta.
A major transgression occurred subsequent to Marshybank deposition. The resulting sequence of Dowling and Thistle shales (early to late Santenian) was deposited in a quiet marine basin during a long period of tectonic inactivity. The Hanson and Chungo Members ( late Santonian aged), together, record a single progradational phase prior to the initial major progradation of the Belly River-Paskapoo Assemblage. The bioturbated shales and siltstones of the Hanson Member were deposited well below storm wave base in a quiet marine environment. The lower Chungo member is characterized by a regressive sequence of storm influenced sandstones which exhibit turbidites and hummocky and swaley cross-stratification. The upper Chungo Member at Mt. Yamnuska records tidal dominance within an environment protected from storm events (outer eustuary, protected bay?). At the remaining Chungo exposures the upper Chungo is interpreted in terms of a storm dominated. northeasterly prograding shoreline sequence that was influenced by a strong longshore Current that flowed towards the southeast. The top of the Chungo regression is regionally capped by a thin, transgressive pebble conglomerate which marks the transition into deep marine shales of the Nomad Member.
The late Santonian to early Campanian aged Nomad Member records the last inundation of the Wapiabi Sea. The basal shale beds are transgressive in nature, being deposited above both marine and non-marine Chungo sediments, wgile the transitional upper beds reflect the fast rate at which the non-marine Belly River Formation prograded over the Nomad shales.
Keywords: Geology; Geology